2010
DOI: 10.1055/s-0029-1186199
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial Laser Revascularization Combined with Intramyocardial Endothelial Progenitor Cell Transplantation in Patients with Intractable Ischemic Heart Disease Ineligible for Conventional Revascularization: Preliminary Results in a Highly Selected Small Patient Cohort

Abstract: In this small patient cohort, intramyocardial CD 133+ cell injection combined with transmyocardial laser revascularization led to an improvement in clinical symptomatology in all patients and in left ventricular function in 4 out of 5 patients, with an unclear effect on myocardial perfusion. Caution is advised when employing this therapy in patients with severely depressed left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 95%
“…According to Davy et al [16] enrichment of autologous bone marrow CD34 + stem cells could increase the efficacy of treatments in clinical settings. Despite the fact that CD34 + cells have been the selected option for heart repair, there are also some reports of CD133 + cells applied in clinical trials showing improvement of myocardial viability and local perfusion of the infarcted zone [17][18][19][20][21][22]. However, none of these studies have shown de novo formation of cardiac muscle.…”
Section: Introductionmentioning
confidence: 95%
“…The presence of different numbers or impaired function of pro-angiogenic hematopoietic cells in different disease states supports their role as mediators of vascular health. They have, for instance, been demonstrated to correlate with degree of cardiovascular disease, severity of pulmonary hypertension, cancer, and diabetes [44,45] [612,15,32]. They have been demonstrated to be derived from the marrow and home in to sites of vascular remodeling [612].…”
Section: Origin and Function Of Pro-angiogenic Hematopoietic Cells Anmentioning
confidence: 99%
“…They have, for instance, been demonstrated to correlate with degree of cardiovascular disease, severity of pulmonary hypertension, cancer, and diabetes [44,45] [612,15,32]. They have been demonstrated to be derived from the marrow and home in to sites of vascular remodeling [612]. Furthermore, preliminary trials have demonstrated a possible therapeutic role for these cells in cardiovascular disease [612].…”
Section: Origin and Function Of Pro-angiogenic Hematopoietic Cells Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit using a time-optimized accelerated procedure protocol, the procedure resulted in a high-quality cell product in terms of purity as well as vitality. This approach was presented for the first time in a small cohort study in patients with intractable ischemic heart disease who received laser treatment and CD133+ cell transplantation [11].…”
Section: Discussionmentioning
confidence: 99%